Stress Management among Senior Academic Administrators in Ghana’s Public Universities: A Cross-Sectional Design Study - Abilla Buame, Juliana; J. Tiika, Bernard; Mensah Nyamadi, Victoria (Researchparks Publishing, 2025)
Abstract This study explores the sources of stress among administrative staff in Ghana's Public Universities, focusing on their socio-demographic characteristics, work experience, schedules, and stress management strategies. A total of 90 respondents participated, exhibiting a diverse age range predominantly between 26-55 years, with a significant gender imbalance favoring females (66.7%). The analysis reveals that 46.7% of participants have over ten years of experience in their roles, primarily working regular 9-5 hours (83.3%). The findings indicate that travel distance, work breaks, and overtime patterns significantly influence stress. A notable 83.3% of respondents report that travel distance increases their stress levels. Furthermore, 93.3% are unaware of university-provided stress management programs, and most of those who have attended stress management training workshops perceive them as ineffective. Recommendations for improving staff well-being include implementing health and wellness programs, enhancing work-life balance, providing stress management education, and improving on work environments. These insights underscore the urgent need for effective interventions to mitigate stress and foster a healthier workplace culture.